Validation of nickel isotopes neutron cross sections using nickel spherical benchmark. (October 2018) - Schulc, Martin; Košťál, Michal; Novák, Evžen; Czakoj, Tomáš
Abstract: The fast leakage neutron spectra have been measured on spherical nickel benchmark assembly of diameter 50 cm. The 252 Cf neutron source with approximate emission of 5.0·10 8 n/s was placed into the centre of the sphere. Fast neutron spectrum in the range of 1–10 MeV was measured in the distance of 1 m from the sphere centre by means of proton recoil method using scintillation stilbene crystal. The experimental data were compared to transport calculations based on several evaluated nuclear data libraries using MCNP6. MCNP6 was compared with SCALE/MONACO program using the same ENDF/B-VII.1 library which leads to different differential neutron flux results. Best experimental agreement with calculation in MCNP6 is achieved with ENDF/B-VII.1 library. Contrary, worst agreement is achieved with JENDL-4.0 and CENDL-3.1 libraries. Furthermore, cross section sensitivity analysis for elastic and inelastic scattering for both main nickel isotopes ( 58 Ni, 60 Ni) was performed. It was shown that 58 Ni isotope has higher influence on the result than 60 Ni isotope in the entire energy range under study. The highest influence has the elastic XS of 58 Ni around energy of 1.5 MeV. The inelastic cross section (XS) of 58 Ni dominates in the energies above 2 MeV where two percent rise due to the inelastic XS leads up to 3.3% decrease in the neutron flux. Highlights: Measurement of fast neutron flux penetrating through nickel sphere. Effect of different data libraries on calculations. Comparison of MCNP6 and SCALE/MONACO codes. Sensitivity analysis of 58 Ni, 60 Ni elastic and inelastic cross sections.